2010
DOI: 10.1088/1367-2630/12/7/075019
|View full text |Cite
|
Sign up to set email alerts
|

Motional effects on the efficiency of excitation transfer

Abstract: Abstract. Energy transfer plays a vital role in many natural and technological processes. In this work, we study the effects of mechanical motion on the excitation transfer through a chain of interacting molecules with applications to biological scenarios of transfer processes. Our investigation demonstrates that, for various types of mechanical oscillations, the transfer efficiency is significantly enhanced over that of comparable static configurations. This enhancement is a genuine quantum signature and requ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…This global coupling of a single mode to the exciton chain yields spatially correlated excitonic fluctuations along the chain [28][29][30]. This is similar to other vibrationally enhanced transport schemes, such as [24,31], but in our case we do not consider any external driving of the common vibrational mode. Instead we will show that the initial excitation of the jth site will excite the coupled vibrational mode and the resulting exciton-vibrational dynamics induces directed exciton transport.…”
Section: Modelsupporting
confidence: 55%
“…This global coupling of a single mode to the exciton chain yields spatially correlated excitonic fluctuations along the chain [28][29][30]. This is similar to other vibrationally enhanced transport schemes, such as [24,31], but in our case we do not consider any external driving of the common vibrational mode. Instead we will show that the initial excitation of the jth site will excite the coupled vibrational mode and the resulting exciton-vibrational dynamics induces directed exciton transport.…”
Section: Modelsupporting
confidence: 55%
“…To study dissipationless quantum excitation energy transport (EET) in the network, we use the evolution of the master equation in the Markovian approximation as follows 33,34 :ρ…”
Section: 17mentioning
confidence: 99%
“…Recently 2D electronic spectroscopy demonstrated that the excitation energy transfer in photosynthetic complexes could involve long-lived quantum coherence [13][14][15][16][17][18][19]. These experimental observations have lead to vigorous theoretical efforts to study quantum coherent dynamics in light-harvesting complexes [20][21][22][23][24][25][26][27][28][29] and observations of environment-assisted quantum transport [20,21,24]. Moreover, various ways for partitioning the contribution of quantum coherence to the energy transfer efficiency (ETE) have been explored [23,25,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%